2009
DOI: 10.1007/s11886-009-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

Emerging inflammatory markers for assessing coronary heart disease risk

Abstract: Although assessment of traditional coronary heart disease risk factors can often stratify individuals into low- or high-risk categories, additional means are needed to more precisely classify people clinically defined as intermediate-risk, to guide the intensity of risk-reducing therapies. The recognition that inflammatory pathways are important in the progression of atherosclerosis and its complications has prompted investigation to identify circulating risk markers that may be useful in risk stratification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Therefore, predicting the risk for CAD in patients with MetS at the early stages is important for targeting prevention strategies. In recent years, serum biomarkers have emerged as important tools for prediction, diagnosis, risk stratification and therapeutic decision-making for patients with cardiovascular disease (6). In the current study, elevated serum chemerin level was found to be an independent predictive marker of the presence of CAD in subjects with MetS.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Therefore, predicting the risk for CAD in patients with MetS at the early stages is important for targeting prevention strategies. In recent years, serum biomarkers have emerged as important tools for prediction, diagnosis, risk stratification and therapeutic decision-making for patients with cardiovascular disease (6). In the current study, elevated serum chemerin level was found to be an independent predictive marker of the presence of CAD in subjects with MetS.…”
Section: Discussionmentioning
confidence: 49%
“…This indicates that chemerin may play a considerable role in MetS and might be a potential independent adipocytokine marker of MetS. In addition, obesity, hypertension, dyslipidemia and inflammation have been suggested to be associated with increased risks for CAD (6). We then hypothesize that the levels of serum chemerin may be correlated with the development of CAD in patients with MetS.…”
Section: Introductionmentioning
confidence: 91%
“…Several types of secretory PLA 2 ( 16,17 ) and the lipoprotein-associated PLA 2 (Lp-PLA 2 ) that preferentially hydrolyses oxidized PCs in LDL ( 18 ) provide biomarkers of infl ammation and atherosclerosis [reviewed in (19)(20)(21)(22)]. Moreover, Lp-PLA 2 has emerged as a causative agent of atherosclerosis and as a new therapeutic target ( 17,(23)(24)(25)(26)(27).…”
Section: Ldl Enrichment With Exogenous Oleic Acidmentioning
confidence: 99%
“…Eine erhöhte Expression von löslichem CD40 L ist bei Autoimmunerkrankungen wie der RA in Verbindung mit der Krankheitsaktivität bekannt [34,35]. Ebenso ist das Glykoprotein sCD40 L bekannt als Marker für die entzündliche Krankheitsaktivität bei koronarer Herzkrankheit [36]. Der Anstieg der sCD40 L-Spiegel unserer Patienten steht klar in Verbindung mit einer Steigerung der Entzündungsaktivität, wie die formale Korrelation zu den Entzündungsparametern CRP und BSG ergab.…”
Section: Schlüsselwörterunclassified